A linha do horizonte não divide o mundo que tem à frente: Entrevista com o artista L. C. Vinholes - Loreto, Mari Lucie da Silva (Paralelo 31, 2019)
Esta entrevista, realizada em novembro de 2018, rememora a trajetória criativa e poética do artista pelotense L.C. Vinholes, abordada pela exposição retrospectiva que abriu no mesmo mês, L.C. Vinholes: constelações e fronteiras dissipadas, realizada pelo Museu de Arte Leopoldo Gotuzzo – MALG da Universidade Federal de Pelotas/UFPel. The horizon line does not divide the world ahead: Interview with the artist L. C. VinholesAbstract:This interview, which took place in November of 2018, recalls the creative and poetic trajectory of the artist, native to Pelotas, RS, Brazil, L.C. Vinholes, and addresses his retrospective exhibition which opened the same month: L.C. Vinholes: constellations and dissipated frontiers, at the Museum of Art Leopoldo Gotuzzo - MALG of the Federal University of Pelotas(UFPel), Pelotas, RS, Brazil.